Intimate Partner Violence and Neighborhood Income: A Longitudinal Analysis - Bonomi, Amy E. (Violence Against Women, 2014)
This investigation used a longitudinal design to examine the relationship between neighborhood-level income, individual-level predictors, and police-reported intimate partner violence in 5,994 urban couples followed over 2 years. At the baseline abuse incident, intimate partner violence rates were highest in the poorest neighborhoods (13.8 per 1,000 women in the lowest income quartile, followed by 12.1, 8.2, and 5.0 in the respective higher income quartiles). However, in the longitudinal analysis, weapon use at the baseline abuse event was a much stronger predictor of repeat abuse (incident rate ratios ranging from 1.72 for physical abuse to 1.83 for non-physical abuse) than neighborhood income.